Harmonized system of quality assessment for electronic components. Fixed resistors for use in electronic equipment. Blank detail specification: fixed resistor networks with individually measurable resistors of either different resistance values or different rated dissipations. Assessment level E Part 04.02, (15th July 1984) - British Standards Institution,
No abstract available